PENGARUH NILAI NASABAH, KUALITAS PRODUK, KUALITAS JASA SYARIAH DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH DI BANK SYARIAH MANDIRI KUDUS - Sof'an, Muhammad; Supriyadi, Supriyadi (EQUILIBRIUM, 2016)
This study used field research approach by questionnaire distributed to 100 customers of Syariah Mandiri Bank. The samples were taken using accidental sampling and the data were analyzed using multiple linear regression analysis. The results were: first, the customer value has an influence on customer loyalty with tcount 3,034 > ttable 1,984 and significance level below 5%. Second, the product quality has an influence on customer loyalty with tcount 3,166 > ttable  1,984 and significance level below 5%. Third, the service quality has an influence on customer loyalty with tcount 2,976 > ttable 1,984 and significance level below 5%. Fourth, the Customer satisfaction has influence on customer loyalty with tcount 2,799 > ttable 1,984 and significance level below 5%.